A COMPARISON MENTAL HEALTH, PHYSICAL SYMPTOMS, ANXIETY AND SLEEPING DISORDERS AND DISORDERS IN SOCIAL FUNCTION AMONG MALE AND FEMALE ATHLETES AND NONATHLETES STUDENTS - Nili Ahmadabady Zahra; Hoseini Rastegar; Hoseini Mahri (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Purpose: The purpose of this study was to comparison mental health, Physical symptoms, Anxiety and sleeping disorders and Disorders in social function among male and female athletes and non-athletes students. Methods: The target population consisted entirely male of female athletes and non-athletes students in University of Guilan. After translate of standard General Health Questionnaires (GHQ), and adjust of some question, questionnaires were evaluated by professors of faculty of physical education and sport sciences. The reliability guided Cronbach Alpha value of (0.83). Among them 90 male athlete and 90 male non-athlete with mean. The collected data was analyzed by t-test, one-way ANOVA. Result: There were significant difference mean scores between in four mental health scales, physical symptoms, anxiety and sleep disorders and impaired social functioning athlete and non-athlete in both groups. Conclusion: Therefore, with fewer psychological problems in an athlete, physical activity can be purpose strategies as appropriate, easy and inexpensive to improve mental health among male and female non- athlete students.